The effect of blooket on students’ grammar mastery - Amalia, Fitri; Sujarwati, Iis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
A group of researchers investigated the impact of Blooket on students' vocabulary mastery and noted that this interactive educational tool could also enhance grammar skills. However, studies specifically examining Blooket's influence on grammar mastery are limited. This research aimed to investigate the effect of Blooket on students' grammar mastery. The study employed a quasi-experimental, which involved 156 ninth-grade students at SMP Negeri Karang Jaya during the 2024/2025 academic year. Using cluster random sampling via a lottery system, participants were divided into experimental and control groups. To assess grammar mastery, both pre-tests and post-tests were administered. The results from the paired sample t-test indicated a significance level of p < 0.05 (0.000 < 0.05), demonstrating a notable improvement in the grammar mastery of the experimental group after using Blooket. Additionally, the independent sample t-test comparing the experimental and control groups yielded a significance level of p < 0.05 (0.044 < 0.05), confirming that Blooket positively influenced the students' grammar mastery. This study underscores the potential of game-based learning tools like Blooket in enhancing educational outcomes related to grammar.